Measuring the Global Virtual Teams (GVTs) performance: confirmation study - Gheni, Ali Yahya; Jusoh, Yusmadi Yah; A. Jabar, Marzanah; Mohd Ali, Norhayati (Indian Society for Education and Environment, 2017)
Objectives: This paper found that there is a need to propose a framework to measure the global virtual teams’ performance involving online training and development, organizational commitment, and motivation in global IT projects. Also this research aims to examine the relationship among online training and development, organizational commitment, motivation, and virtual teams’ performance in global IT projects success, propose a framework to assist the project manager to measure the global virtual teams’ performance in global IT projects involving the online training and development, organizational commitment, and motivation based on defined measures and Key Performance Indicators (KPIs) for the global virtual teams in global IT projects which is our contribution for this study. Method: The Confirmation study were conducted which is including study (expert-questionnaire interview, pilot study, and empirical study (the survey) then the framework proposed. The proposed framework was evaluated through experts from academics and industries. Findings: The results of the confirmation/preliminary study confirmed the validity of the conceptual framework and the validity and reliability of the instrument. Confirmation/empirical study were verified the conceptual framework and the final framework was proposed. Applications: This framework is to assist the project manager to measure the global virtual teams’ performance in global IT projects.